The Warsaw´s Hospital of Toulouse, a project of the Spanish exile - Pablo Molanes Perez (Universidad de Alicante, 2013)
The failed invasion of Arán Valley during Operation Reconquest developed in October 1944 made it necessary to establish a hospital to take care of the sick and injured from the operation. In October 1944, the Warsaw Hospital is opened in the Saint Cyprien neighborhood of Toulouse. The objective of this article is to do a critical revision of the history of the hospital during the Spanish stage, basing our reflexion on the available publications and primary sources. The presence of numerous refugees in need of medical care and the failure of the military operations contribute to the hospital's transformation into a center of free care for the exiled civil population and also a meeting place. The center receives international aid, principally from the Join Anti-Fascist Refugee Committee distributed through the humanitarian organization Unitarian Service Committee. The hospital is instituted with the aim of being a model republican hospital so as to be implemented with the return of a democratic regime in Spain. As a result of the anticommunist campaign at the onset of the cold war the hospital is accused of being a "refuge of soviet agents". On 7 September of 1950, during Operation Bolero-Paprika, 50 people are imprisoned in Toulouse, amoung them the medical staff at the Warsaw hospital. The project was cut short by the change in international politics but managed to be saved thanks to the involvement of French doctors and the economic support of the PCF, guaranteeing its survival as a welfare center until nowadays.